Oath of honor [large type] : a thriller - Betley, Matthew (Thorndike Press, 2017)
A break-neck, edge-of-your-seat thriller that moves from a resurgent Russian threat in the Aleutian Islands to North Korean spy ships to secret Sudanese prisons as former Marines Logan West and John Quick, now members of an FBI special task force, uncover a global conspiracy that threatens America's position in the current international balance of power. Logan West and John Quick are sent to Dutch Harbor, Alaska, to investigate the possible presence of a Russian black ops team on a mission to steal United States next-generation technology. The resulting violent confrontation triggers a global search for the stolen technology and threatens to pit the US against China in a looming shadow war and technology race. As Logan and John--joined by the chief of the CIA's Special Operations Group, Cole Matthews--battle their way through Spain, the Mediterranean, and ultimately, across Sudan, an imminent threat arises at home that FBI Deputy Director Mike Benson must face and determine if it is part of the deadly global conspiracy. -- Amazon.com.